Selecting the Right Plane of Dissection in Thyroidectomy: Along the Recurrent Laryngeal Nerve or the Thyroid Capsule? A Retrospective Analysis - Waseem, Talat; Ahmed, Safia Zahir; Zahara, Fatima Tuz; Ashraf, Muhammad Hasham; Azim, Khwaja Muhammad (International Archives of Otorhinolaryngology, 2021)
Introduction Total thyroidectomy remains highly technical, with a significant risk of recurrent laryngeal nerve (RLN) compromise and hypoparathyroidism. After identifying RLN, at the level of the ligament of Berry, local factors may compel the surgeon to either dissect along the nerve or the thyroid capsule.Objective The objective of the present study is to compare these two approaches in terms of outcomes and complication rates.Methods This is a retrospective analysis from September, 2013 to April 2019 of 511 consecutive patients undergoing thyroidectomy. General demographics and disease parameters were recorded. At the discretion of the surgeon and according to the demands of the local operative factors, the patients either had dissection along the RLN or along the thyroid capsule. Perioperative and postoperative parameters such as blood loss, duration of surgery, hospital stay, pain scores, analgesia requirements and complications were recorded. The groups were compared with the Pearson chi-squared test or with the Fisher exact test. A p-value < 0.05 was considered statistically significant.Results The incidence of transient hypocalcaemia and transient RLN compromise were higher when dissection was performed along the nerve as opposed to the plane along the thyroid capsule. Other parameters including operative time, hospital stay, pain scores, analgesia requirement, wound infection, seroma, hemorrhage, and recurrence did not differ between the groups. Subgroup analysis of the patients who presented with complications showed that local factors, malignancy, and extent of surgery correlated positively with complications when dissected along the RLN.Conclusion Dissection along the capsule of the thyroid during thyroidectomy is a safer plane in terms of low rate of transient RLN injury and hypoparathyroidism as opposed to dissection along the nerve.
Keywords: dissection; thyroidectomy; plane of dissection; recurrent laryngeal nerve injury; hypoparathyroidism